EVIDENCE FOR INDUCED SEISMICITY FOLLOWING THE 2001 SKYROS MAINSHOCK - Adamaki, A.K.; Tsaklidis, G. M.; Papadimitriou, E. E.; Karakostas, V. G (Bulletin of the Geological Society of Greece, 2010)
Estimation of the seismicity rate changes caused by a major earthquake is based upon the assumption that the earthquake occurrence can be described by stochastic processes. Three stochastic models are applied to the data, i.e. the homogeneous Poisson model, the non-homogeneous Poisson model with two different rate functions, and the Autoregressive model AR(2). The two latter models seem to be adequate to properly simulate the earthquake production in a given area. The identification of the model which best fits the data, enables the estimations of the seismicity rate changes and the numbers of the earthquakes following a specific main shock.